PENGARUH KONSELING REALITA TERHADAP PEMBENTUKAN IDENTITAS DIRI SISWA PADA MTS AL-MUSLIMUN NW KEBON KONGOK: The Influence of Reality Counseling On The Formation of Students' Self-Identity at MTs Al-Muslimun NW Kebon Kongok - Hariadi, Ripan; Zulaifi, Reza (Yayasan Al-Amin Qalbu, 2024)
The purpose of this research is to see the influence of reality counseling in forming students' self-identity. The research method used in this research is an experimental method using a one group pre-test post-test only research design. The results of data analysis obtained were 7,794 and the t-table value at the 5% significance level with dk=12 was 1,782, this shows that the calculated t is greater than the t table (7,794>1,782), which means Ho is rejected and Ha is accepted which reads : There is an influence of reality counseling on the formation of students' self-identity at MTs Al-Muslimun NW Kebon Kongok